SENYAWA TRITERPENOID DARI EKSTRAK N-HEKSANA KULIT BATANG TANAMAN Garcinia benthami - Elya1, Berna; Kosela, Soleh; Muhammad, Muhammad (Makara Journal of Science, 2009)
Triterpenoids compounds from N-hexane extract of the stem bark of Garcinia benthami. Two triperpenoids compounds, i.e. friedelin (1) and 3β-hydroxy-lanosta-9(11),24-dien-26-oic acid (2) were isolated from the n-hexane extract of the stem bark of Garcinia benthami. The structures of these compounds were elucidated by IR, MS,1 H-NMR and 13C-NMR spectroscopy and by comparison of their spectroscopic data with those reported data from the literature.